Forgetting "Novel" but Not "Dragon": The Role of Age of Acquisition on Intentional and Incidental Forgetting - Marful, Alejandra; Gómez-Ariza, Carlos J; Barbón, Analia; Bajo, Teresa (PLOS One, 2017)
Two experiments studied how the age at which words are acquired (Age of Acquisition, AoA) modulates forgetting. Experiment 1 employed the retrieval-practice paradigm to test the effect of AoA on the incidental forgetting that emerges after solving competition during retrieval (i.e., retrieval-induced forgetting, RIF). Standard RIF appeared with late-acquired words, but this effect disappeared with early-acquired words. Experiment 2 evaluated the effect of AoA on intentional forgetting by employing the list-method directed forgetting paradigm. Results showed a standard directed forgetting effect only when the to-be-forgotten words were late-acquired words. These findings point to the prominent role of AoA in forgetting processes.
Keywords: JCR; Scopus